Student-centered learning: The need for value injection. - Poh, Boon Lian * (2013)
Student-centred learning (SCL) refers to an educational environment where students are actively involved in what they are studying with teachers as facilitators. Based on the observations of the author on diploma students, she found there was a gap between the seven tenets of SCL found in literatures and what the students were expected and capable of. The inability of students to read and write effectively in English and poor time management were two common problems encountered. The current generation grew up in an era of the Internet and smartphones and they are used to short messages and are overloaded with information. This is also the era when college education is commonly available. As such, in pursuance of SCL, teachers may mistakenly tailor teaching according to the characteristics of the students hence further impair their inability to study effectively. To be truly student-centred, educators need to prepare them for society’s on-going needs and demands. There is a need to inject values that will help the students to achieve their goals in college and their working life. The three main aspects would be to embrace the idea of being hard-working, to persevere in improving the command of English language and to have good time-management which involves discipline. This is consistent with the idea of the Beliefs-Values-Rules (BVR) belief system.